The Development of Information Technology and Its Influence on the Field of Management Accounting - Riinawati Riinawati (STIE Jambatan Bulan, 2021)
This study aims to determine the impact of the development of information technology in the field of management accounting. The method used is descriptive qualitative research methods and library research methods. The results of this study include the development of information technology that has brought important changes to the business world. There are many types of information systems that use emerging information technologies, including electronic data processing systems, data processing systems (DPS), decision support systems (DSS), data processing systems, management information (MIS), executive information systems (EIS), expert system (ES)) and Accounting Information System (AIS). The development of information technology has also influenced the field of management accounting because it is a field where information is generated in the context of management planning, control, and decision making. These impacts can be beneficial or detrimental to the business.